2021
DOI: 10.3389/fmolb.2021.657161
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division Cycle Associated Genes as Diagnostic and Prognostic Biomarkers in Hepatocellular Carcinoma

Abstract: With high mortality and poor prognosis, hepatocellular carcinoma (LIHC) has become the fourth leading cause of cancer-related deaths worldwide. Most of the LIHC patients missed the best treatment period because of the untimely diagnosis. For others, even if they are temporarily cured, they have to face a very low prognostic survival rate and a very high risk of recurrence. Based on the characteristics of abnormal proliferation and uncontrolled growth of tumor cells. Cell Division Cycle Associated (CDCA) family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Cell Division Cycle Associated (CDCA) family genes were proven to be associated with survival in HCC patients with the hepatitis virus or alcohol consumption. One of the most relevant neighboring genes to CDCAs in HCC was SGO2 [26]. At present, the therapeutic efficacy of targeted treatment and immunotherapy is still unsatisfactory [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Division Cycle Associated (CDCA) family genes were proven to be associated with survival in HCC patients with the hepatitis virus or alcohol consumption. One of the most relevant neighboring genes to CDCAs in HCC was SGO2 [26]. At present, the therapeutic efficacy of targeted treatment and immunotherapy is still unsatisfactory [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It is often overexpressed in different tumor tissues, such as gastric cancer [24]. Moreover, some researchers have discovered that SGO2 may be combined with other genes to participate in partial tumor occurrences and developments in recent years [26,27]. However, the biological function of SGO2 in HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the abnormal expression of PLOD1 is closely associated with multiple malignancies in humans, including stomach cancer, colorectal cancer, liver cancer, and osteosarcoma [12][13][14][15] . n addition, Yamada Y et al [16] , indicated that miR-140-5p could directly bind to the 3'-UTR of PLOD1, causing PLOD1 knocking to signi cantly inhibit the migration and invasion of T24 cells.Jiang H et al [15] ,found that PLOD1 regulated the proliferation and invasion of osteossarcoma cells through the Wnt/ β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…AGING A growing body of evidence indicates that SGOL2 is a novel molecule with profound significance in cancer and related fields. Up to now, what is clear is that SGOL2 has been reported as a differentially expressed gene in various types of cancer, including glioma, hepatocellular cancer, and endometrial cancer [13][14][15]. Previous studies had demonstrated that SGOL2 had a protein-protein interaction with BRCA1, whose variants were regarded as biomarkers to predict the survival prognosis of prostate cancer patients [16,17].…”
Section: Introductionmentioning
confidence: 99%